Structure Identification of Nanopowder TiO2 Synthesized by Coprecipitation Method: Vicran Zharvan, Gatut Yudoyono, Darminto Darminto - Vicran Zharvan Vicran Zharvan; Gatut Yudhoyono Gatut Yudhoyono; Darminto Darminto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2023)
Titanium dioxide, or TiO2 is a semiconductor material with many advanced applications, such as photocatalysts. Generally, TiO2 has three primary forms of crystal structure: anatase, brookite, and rutile. Among these types of crystal structures, anatase has good properties in photocatalysts application due to its band gap value (3.20eV) and stability. Further, there are many methods to synthesize TiO2, such as sol-gel, hydrothermal method, etc. Still, the copreciptation method has a suitable method because it is easy to produce, high pure product and low cost. However, many parameters control the quality of TiO2 itself: pH, temperature, time and mechanical process. Especially for the mechanical process, no results were reported about structure identification of TiO2 at mixing time below 25 hours. In this research, titanium dioxide (TiO2) powder has been investigated using coprecipitation method and TiCl3 as a raw material. The TiO2 was synthesized by mixing the time duration at 5, 10 and 25 hours in this method. Analysis using x-ray diffraction shows that all the samples have an anatase phase. Further, Rietveld refinement analysis shows that mixing duration time does not significantly affect the lattice parameters.